Cerodontha (Dizygomyza) handlirschi (Diptera Agromyzidae) Nowakowski new far Italian fauna, and the description of a malformation (Bollettino di zoologia agraria e bachicoltura, 2024)
Cerodontha handlirschi Nowakowski collected on Central Alps (Alpi Retiche), new for the Italian fauna is reported. A malformation on antennae of a male is described and illustrated.
Keywords: Cerodontha handlirschi; Agromyzidae; Italian fauna; malformation